Generation of an iPSC line from congenital hypopituitarism patient with a nonsense heterozygous variant in FOXA2 - Camilletti Maria Andrea; Chirino Felker Gonzalo Tomás; Castañeda Sheila; Zabalegui Federico; Amin Guadalupe; Belgorosky Alicia; Ciaccio Marta; Di Palma Maria Isabel; Vaiani Elisa; Waisman Ariel; Miriuka Santiago; Pérez Millán María Inés; et al. (Stem Cell Research, 2025)
Forkhead box A2 (FOXA2) is a pioneer transcription factor, necessary for human development. Mutations in FOXA2 were recently associated with congenital hypopituitarism (CH); however, the pathogenic mechanism remains unknown. Induced pluripotent stem cells from a patient with CH carrying a heterozygous FOXA2 variant (c.686C > A; p.S229*) were obtained by cellular reprogramming from the patient’s peripheral blood mononuclear cells. The generated iPSCs exhibited all hallmarks of pluripotency, differentiated into the three germ layers, and presented a normal karyotype. This resource represents a valuable tool for investigating the role of FOXA2 in pituitary development and associated disorders.